Given that the transverse axis of a hyperbola is the x-axis, the re-written in the standard form,
a = 3
b = 1
c = 12.
It is to be noted that the standard form of a linear equation is given as:
ax + by = c
Rewritten in the normal format,
y=± (4)/(3)x ⇒ y-4 = -3 (x-3)
Simplifying -3(x-3) by applying distributive property and we have:
-3x -3 * -3
Hence
y-4 = -3x -3 * -3
⇒ y-4 = -3x + 9
Collecting like terms on one side of the equation we have
3x + y - 4 = 9
⇒ 3x + y = 9+4
⇒ 3x + y = 12 = Standard Form
Therefore, in standard from,
a = 3
b = 1
c = 12
See the relevant Graph attached.
Learn more about hyperbola at:
https://brainly.com/question/3405939
#SPJ1